Composite Tracking Control for Generalized Practical Synchronization of Duffing-Holmes Systems with Parameter Mismatching, Unknown External Excitation, Plant Uncertainties, and Uncertain Deadzone Nonlinearities - Yeong-Jeu Sun (Abstract and Applied Analysis)
The generalized practical synchronization (GPS) of uncertain Duffing-Holmes chaotic systems with parameter mismatching, unknown external excitation, plant uncertainties, and uncertain deadzone nonlinearities is investigated. Based on the composite control approach, a tracking control is derived to realize the GPS for the uncertain Duffing-Holmes chaotic systems with parameter mismatching, unknown external excitation, plant uncertainties, and uncertain deadzone nonlinearities. Besides, the guaranteed exponential decay rate, convergence radius, and desired scaling factor can be prespecified. Finally, numerical simulations are provided to illustrate the feasibility and effectiveness of the proposed GPS scheme.